A novel event-triggered communication strategy for second-order multiagent systems. (February 2020) - Li, Tao; Zhao, Hui; Chang, Yu
Abstract: This paper concentrates on the design of an event-triggered communication strategy for secondary multi-agent systems. Many existing results in this field usually require centralized information depending on the Laplacian matrices. In a real application, however, such the constraint is conservative. To address it, this paper proposes an event-triggered sampling mechanism for interagent communication with updated thresholds. Accordingly, consensus protocols with adaptive coupling control gains are proposed for both a fixed topology and switching topologies. It is proven that the proposed method guarantees the leader-following consensus for second-order multiagent systems with an arbitrarily connected topology and even with jointly connected switching topologies. The effectiveness of the proposed scheme is verified by simulation examples. Highlights: An adaptive event-triggered strategy makes MASs independent of spectrums of Laplacian matrices. A fully distributed protocol for nonlinear MASs eases the burden of communication channels. The networking protocol can be easily generalized to jointly connected switching topologies.